1998
DOI: 10.1007/s001060050198
|View full text |Cite
|
Sign up to set email alerts
|

Anteriores Pseudodivertikel nach Laryngektomie

Abstract: An anterior neopharyngeal pseudodiverticulum is a mucosal pouch located between the tongue and hypopharynx due to an epiglottis-like posterior tissue band that forms after total laryngectomy. This condition has rarely been mentioned in literature. Incidence, symptoms, treatment, and possible etiologic factors were examined. Twenty post-laryngectomy patients were questioned about swallowing disorders and were examined clinically and by barium swallow. Eleven patients were found to have a pseudodiverticulum, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…Further studies have confirmed these findings. 8,21 Fistula formation has also been disproved as a cause of pseudo-epiglottis. 2,6,22,23 Dysphagia after laryngectomy is a common problem, varying from 10% to 60%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies have confirmed these findings. 8,21 Fistula formation has also been disproved as a cause of pseudo-epiglottis. 2,6,22,23 Dysphagia after laryngectomy is a common problem, varying from 10% to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In addition to the above, dysphagia outcomes following surgical repair of pseudo-epiglottis utilizing the carbon dioxide (CO 2 ) laser have only been reported in three studies to date, again without the use of pre-and post-operative measurements of dysphagia using a validated questionnaire. [6][7][8] Oursin et al and Pitzer et al reported complete resolution of dysphagia after pseudo-epiglottis division in 88% of their patients, 6,8 while 100% improvement in dysphagia post-operatively was noted in all three patients in a case series article. 7 Dysphagia following laryngectomy is common and multifactorial in etiology, with an incidence ranging from 10% to 60%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The body of literature on treatment effects of OD after TLE remains poor and there is no consensus on the diagnosis and treatment of OD for this population [434]. Some studies showed preliminary promising results of botulinum toxin injections, endoscopic dilatations, and TOLS [441][442][443][444][445][446][447][448]. However, significant treatment effects or trends of these techniques were not found.…”
Section: Oropharyngeal Dysphagia Following Total Laryngectomymentioning
confidence: 99%
“…Jól vizualizálható retrocricoid régió bal oldali endoszkópos arytenoid abdukciós lateropexia közben. 1) Bal oldali kannaporc, 2) retrocricoid terület, 3) hátsó garatfal, *: endolaryngealis fonalvezető eszköz ÖSSZEFOGLALÓ KÖZLEMÉNY diverticulum eltávolítása laryngectomiát követően, nyelőcsőpolip eltávolítása, gégeplasztika, idegentest-eltávolítás vagy a cricopharyngealis izom endoszkópos myotomiája [13][14][15][16][17][18][19]. A feltáró fő előnye, hogy mérete egyénileg állítható még a behelyezés után is.…”
Section: áBraunclassified